Dynamic Oligopolies with Time Delays - Matsumoto, Akio (Springer Singapore, 2018)
This is the first book to comprehensively examine the asymptotic behavior of dynamic monopolies, duopolies, and oligopolies where firms face information and implementation delays. It considers discrete and continuous timescales, continuously distributed delays, as well as single and multiple delays. It also discusses models with linear and hyperbolic price functions in three types of oligopolies: Cournot competition with quantity-adjusting firms, Bertrand competition with price-adjusting firms, and mixed oligopolies with both types of firms. In addition to the traditional Cournot-Nash equilibria, it introduces cases of partial cooperation are also introduced, leading to the analysis of cartelizing groups of firms and possible governmental actions against antitrust behavior. Further, the book investigates special processes for firms learning about the uncertain price function based on repeated market information. It addresses asymptotic properties of the associated dynamic systems, derives stability conditions, identifies stability switching curves, and presents in global analyses of cases of instability. The book includes both theoretical results and computer studies to illustrate and verify the theoretical findings.